Biogeochemical Cycling of Carbon and Nitrogen in Rainfed Rice Production Under Conventional and Organic Rice Farming: 10.32526/ennrj/20/202200019 - Kaiphoem, Juthamard; Sornhiran, Natcha; Leksungnoen, Parapond; Saentho, Apinya; Nansahwang, Arnon; Khunthong, Sutdacha; Aramrak, Surachet; Prakongkep, Nattaporn; Wisawapipat, Worachart (Environment and Natural Resources Journal, 2022)
Dwindling carbon (C) and nitrogen (N) levels in paddy soils decreases rice production and threaten human food security globally. The efficient maintenance of C and N fluxes in soil-rice systems is a crucial prerequisite for agricultural and environmental sustainability. Herein, we examined the C and N fluxes from 63 rainfed rice paddy fields under conventional farming (CF) and organic farming (OF) systems in Thailand. The C and N fluxes were measured based on a detailed analysis of relevant influxes (fertilizer, manure, and biomass addition) and effluxes (biomass harvest and greenhouse gas emission). The results demonstrated that the harvested grain and straw contributed to the most abundant C and N effluxes for both farming systems. The CH4 effluxes were moderate, whereas the N2O effluxes were meager relative to their total effluxes. Stubble incorporation and animal manure addition to soil were the most extensive C influxes. However, the primary N influxes were stubble incorporation and animal manure addition for the OF system, and chemical-N fertilizers for the CF system. Net C depletions were observed in both the CF and OF systems. However, net N was depleted and accumulated in the CF and OF systems, respectively. Straw incorporation to soils could restore the net C accumulations for the CF and OF systems and elevate the net N accumulation for both systems. This study highlighted that complete straw removal has exacerbated the C and N stock in soil-rice systems, inducing insecurity for the environment and the agricultural systems. Effective straw management is a simple approach for sustaining paddy rice production.